2011
DOI: 10.1007/s10508-011-9772-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pre-Existing Affect on the Sexual Responses of Women With and Without a History of Childhood Sexual Abuse

Abstract: Women with a history of childhood sexual abuse (CSA) are at greater risk for experiencing sexual problems in their adult lives. Yet, little is known about the possible role of cognitive and affective mechanisms in the development of sexual arousal difficulties in this population. This study investigated the role of pre-existing affect (affect prior to exposure to sexual stimuli) on genital responses, subjective sexual arousal, and affect elicited during the presentation of erotic film excerpts in a community s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
1
8
0
3
Order By: Relevance
“…Summed PANAS scores were 18.9 ( SD = 6.8) in the week before the interview and 17.4 ( SD = 6.60) in the week after the interview. This is consistent with norms found in two other studies with traumatized populations ( M = 24.1, SD = 9.8; Tull, Barrett, McMillan, & Roemer, ; M = 19.7, SD = 6.6; Vujanovic, Bonn‐Miller, Potter, Marshall, & Zvolensky, ), lower than the mean in a population of urban violence victims ( M = 32, SD = 9.8; Rocha‐Rego et al., ), but higher than the mean in a population of survivors of childhood sexual abuse ( M = 13.6, SD = 3.5; Rellini, Elinson, Janssen, & Meston, )…”
Section: Methodssupporting
confidence: 90%
“…Summed PANAS scores were 18.9 ( SD = 6.8) in the week before the interview and 17.4 ( SD = 6.60) in the week after the interview. This is consistent with norms found in two other studies with traumatized populations ( M = 24.1, SD = 9.8; Tull, Barrett, McMillan, & Roemer, ; M = 19.7, SD = 6.6; Vujanovic, Bonn‐Miller, Potter, Marshall, & Zvolensky, ), lower than the mean in a population of urban violence victims ( M = 32, SD = 9.8; Rocha‐Rego et al., ), but higher than the mean in a population of survivors of childhood sexual abuse ( M = 13.6, SD = 3.5; Rellini, Elinson, Janssen, & Meston, )…”
Section: Methodssupporting
confidence: 90%
“…Continuous measurement of self‐reported sexual arousal was first introduced by Wincze and colleagues [98] through the creation of a lever that participants could swing in a 90 degree arc to indicate increases and decreases in sexual arousal. A similar device continues to be used at present (e.g., [7,25,49]), along with related devices such as sliders with visual indicators (e.g., [38]) and a computer mouse in which the buttons are used to indicate increases and decreases in sexual arousal (e.g., [80]). When using a continuous recording of self‐reported sexual arousal, researchers usually limit themselves to one question, typically about a global assessment of sexual arousal in the moment.…”
Section: Methodsmentioning
confidence: 99%
“…Traditional models of sexual response emphasize sequential stages of sexual desire, arousal, plateau, and orgasm [5,6] in contrast to more recent theories that indicate sexual response to be a multifaceted phenomenon where sexual arousal and desire are highly overlapping and are influenced by a number of other contextual factors [2]. Research on theoretical models of sexual response supports the multifaceted nature of sexual arousal and acknowledges that while sexual arousal may occur in a traditional linear fashion for some women, others are influenced by a variety of different factors, including, but not limited to, personal history [7,8], psychological mood states [9–11], personality characteristics [12,13], physical health [14,15], and personal attitudes and belief systems [16,17]. Additionally, studies examining female sexual dysfunctions have demonstrated difficulties in differentiating diagnostic groups from each other and healthy controls [18,19], and treatment effect studies have generally produced mixed results in terms of significantly ameliorating sexual response [19].…”
Section: Introductionmentioning
confidence: 99%
“…In theory, negative affectivity in anticipation of sexual activities (anticipatory negative affect) could impair sexual arousal by impacting the ability of women to focus on pleasant stimuli and activating negative expectations, two cognitive mechanisms that can reduce sexual arousal (Barlow, 1986). However it is also worth noting that a recent study did not find that negative affect before sexual stimuli predicted lower physiological and subjective sexual arousal responses to sexual stimuli in women with a history of childhood sexual abuse as compared to women with no abuse histories (Rellini, Elinson, Janssen, & Meston, 2012). Given the dearth of studies on the relation between affect before sexual stimuli and the effects of negative affect on sexual arousal in women with a history of childhood sexual abuse, a replication and expansion of past studies to women with a variety of types of childhood maltreatment, other than sexual abuse, is warranted.…”
Section: Introductionmentioning
confidence: 99%